2018
DOI: 10.3389/fsurg.2018.00017
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Occult Malignancies in Reduction Mammoplasties

Abstract: ObjectivesPatients undergoing reduction mammoplasty (RM) bear the risk of having occult breast cancer nests. The detection rate of malignant neoplasms in the resected specimens, varies greatly in the literature. The aim of our present study was to analyze risk factors and evaluate histopathological findings in our cohort of patients who underwent RM towards our center.Material and methodsIn this retrospective single center study we analyzed 559 female patients [median age 35.99 (±13.34)] who underwent RM betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The cancer rate in patients with no history of breast cancer in previous studies ranged from 0 to 1% 12–26 . Similar to those studies, the cancer rate in our study was 0.36%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The cancer rate in patients with no history of breast cancer in previous studies ranged from 0 to 1% 12–26 . Similar to those studies, the cancer rate in our study was 0.36%.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the rate of AMBL in patients with no history of breast cancer was 3.3%. The previous studies that included only patients with no history of breast cancer reported the rate of AMBL to be between 1.5 and 14% 5,7–26 . The wide range of reported rates of AMBL in different studies can be attributed to different pathological assessment methods of RM specimens between institutions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study of 5781 women represents a large cohort of patients who underwent reduction mammaplasty. The rate of incidentally found breast cancer was consistent with that reported in prior literature (0.06-4.5%) [7,8,11,12].…”
Section: Discussionsupporting
confidence: 90%
“…However, breast cancer is the most common malignant cancer in women [2] and the presence of occult breast cancer in RM specimens has been described before [7,8,11,12]. In previous reports of reduction mammoplasty, the presence of a contralateral breast cancer was found to be a major risk factor for the presence of occult carcinoma [12][13][14]. Preoperative radiologic evaluation is an important tool to reduce the number of carcinomas detected by chance during RM.…”
Section: Discussionmentioning
confidence: 99%